(untitled) (Società e diritti, 2020)
The author proposes an analysis that is able to make the reader understand the complexity and tension between the essential traits of the globalized world and the doctrine of human rights; looking at the case of transnational human trafficking, he illustrates how the tools of globalisation have, on the one hand, contributed to the international diffusion of this modern form of slavery but , on the other hand, have been at the same time protagonists of the expansion of the "rights revolution", represented in a brilliant way by the worldwide affirmation of the victim-centric approach to protecting the trafficked.